Optimization of Counseling by Bhabinkamtibmas to Prevent the Crime of Child Sexual Abuse in the Bandung Police Area - Riskawati Riskawati (Advances in Police Science Research Journal, 2021)
The criminal act of sexual abuse against children in the Bandung Police area has increased every year from 2015-2017, the crime of sexual abuse against children is one of the highest crimes that have occurred in the Bandung Police area where the victims are children aged 13 to 17 who are still in junior high and high school schools. This study uses communication theory, crime prevention, management, the concept of community development units, the concept of community policing, the concept of guidance with counseling, the concept of Law Number 35 of 2014 to analyze existing problems, using a qualitative approach. The focus of the research is the optimization of counseling by Bhabinkamtibmas to prevent criminal acts of sexual abuse against children in the Bandung Police area. The technique of collecting data by means of interviews, observation and document review. This was done with the aim of wanting to know about the criminal act of child sexual abuse in the Bandung Police area. Researchers found that members of Bhabinkamtibmas have carried out counseling well but in its implementation it has not been optimal due to several factors, internal factors that support cooperation between the Binmas Unit and members of Bhabinkamtibmas, existing facilities and infrastructure, special allowances, constraining factors, limited personnel, facilities and infrastructure is still lacking, while external factors that affect the community, religious and community leaders for factors that hinder community participation are still lacking, there is still a lot of unemployment and the distance between Bhabinkamtibmas and the assisted villages. Based on the findings, the authors recommend the need for as many networks as possible in order to prevent criminal acts of sexual abuse against children and the need for special material on criminal acts of sexual abuse against children.